Joint control charts for monitoring location and dispersion - Costa, Antonio F.B. [UNESP]; Machado, Marcela A.G. [UNESP] (My University, 2008)
The T2 and the generalized variance |S| charts are used for monitoring the mean vector and the covariance matrix of multivariate processes. In this article, we propose for bivariate processes the use of the T2 and the VMAX charts. The points plotted on the VMAX chart correspond to the maximum of the sample variances of the two quality characteristics. The reason to consider the VMAX statistic instead of the generalized variance |S| is the user's familiarity with the computation of simple sample variances; we can't say the same with regard to the computation of the generalized variance |S|.
Keywords: Hotelling chart; Multivariate processes; Vmax chart